2016
DOI: 10.1038/nchembio.2148
|View full text |Cite
|
Sign up to set email alerts
|

Cellularly active N-hydroxyurea FEN1 inhibitors block substrate entry to the active site

Abstract: The structure-specific nuclease human flap endonuclease-1 (hFEN1) plays a key role in DNA replication and repair and may be of interest as an oncology target. We present the first crystal structure of inhibitor-bound hFEN1 and show a cyclic N-hydroxyurea bound in the active site coordinated to two magnesium ions. Three such compounds had similar IC50 values but differed subtly in mode of action. One had comparable affinity for protein and protein–substrate complex and prevented reaction by binding to active si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 55 publications
7
55
0
Order By: Relevance
“…Secondly, we showed that binding of compounds 1 – 5 requires the presence of Mg 2+ ions, which bind in the active site of Caf1. This is in agreement with the proposed role of the N ‐hydroxyimide moiety in 1‐hydroxy‐xanthines and related compounds forming ion–dipole interactions with the Mg 2+ ions .…”
Section: Resultssupporting
confidence: 90%
“…Secondly, we showed that binding of compounds 1 – 5 requires the presence of Mg 2+ ions, which bind in the active site of Caf1. This is in agreement with the proposed role of the N ‐hydroxyimide moiety in 1‐hydroxy‐xanthines and related compounds forming ion–dipole interactions with the Mg 2+ ions .…”
Section: Resultssupporting
confidence: 90%
“…In support of our results, other HU-based derivatives have been shown to increase human cell line sensitivity to MMS treatment (Tumey et al 2005;Exell et al 2016) and selectively impair the proliferation of HR-defective cancer cell lines (Exell et al 2016;He et al 2016;Ward et al 2017). Further, in vitro assays have demonstrated that some HU-based compounds are able to enzymatically inhibit the related endonucleases hXPG (Tumey et al 2005) and hEXO1 (Exell et al 2016), but showed species specificity upon testing with bacteriophage T5 FEN and Kluyveromyces lactis XRN1 (Exell et al 2016). These results may explain the mild off-target effects observed for the rad27D and rad52D mutants in our in vivo assays.…”
Section: Discussionsupporting
confidence: 86%
“…Further, based on synthetic lethal genetic interaction relationships, hFEN1 is a second-site target for the selective killing of homologous recombination (HR)-defective and cohesin-mutated cancer cells (McManus et al 2009;van Pel et al 2013). As such, many studies have reported the screening and development of hFEN1 inhibitors as potential anticancer therapeutics (Tumey et al 2005;Dorjsuren et al 2011;McWhirter et al 2013;van Pel et al 2013;Exell et al 2016;He et al 2016;Deshmukh et al 2017).…”
mentioning
confidence: 99%
“…Furthermore, the effect of the combination of ATO and FEN1-KD was also examined in vivo, using a xenograft model in mice. For this study, a previously reported FEN1 inhibitor compound 20 (C20) was used (22,23). C20 is an N-hydroxyl urea derivative that specifically inhibits FEN1 activity, which is the most potent FEN1 inhibitor tested at the time (24).…”
Section: Fen1 Inhibition Enhanced Ato-induced Cytotoxity and Growth Smentioning
confidence: 99%